External Fruit Quality and Harvest Time of Low-Chill Peach and Nectarine Varieties at Santa Fe, Argentina - Giovanelli, Carolina (2014)
Background: We studied low chilling peach varieties recently introduced at the central area of Santa Fe, Argentina, to increase the range of options available to growers of warm-temperate areas. Objective: The aim of this study was to evaluate the external fruit quality and the harvest time of different low-chill peach and nectarine varieties in central Argentina. Results: The harvest period began on the last week of October and extended continuously until the end of December. Although the different varieties ripened in an adequate sequence throughout the season, the second week of November was a critical period in which six varieties reached maturity simultaneously. On the other hand, only a limited number of varieties ripened during the second and fourth weeks of December. Fruit size of peach but not of nectarine showed a positive and significant relationship with the length of the fruit development period. Three peach varieties (‘Flordastar’, ‘Rojo dos’ and ‘San Pedro 1633’) and four nectarines (‘Sunwright’, ‘Nectarine 24’, ‘Carolina’, and ‘Brasil’) produced small fruits (<100 g), which can affect their marketing. Red over-color on the skin was deficient, since only seven varieties developed 50% of red cover. Conclusion: The new varieties tested are suitable for extending the harvest period at the central area of Santa Fe, and will increase the range of options available to growers. However, before recommending its use, internal quality and fruit yield of these varieties should be evaluated for more years.